Age- and Gender-Specific Prevalence of Frailty and Its Outcomes in the Longevous Population: The Chinese Longitudinal Healthy Longevity Study - Wang, Huai-yu; Lv, Xiaozhen; Du, Jian; Kong, Guilan; Zhang, Luxia (Frontiers in Medicine, 2021)
Background Frailty is an epidemic age-related syndrome addressing heavy burden to the healthcare system. Subject to the rarity, age- and gender-specific prevalence of frailty and its prognosis among the longevous population remains under-investigated. Methods Based on the Chinese Longitudinal Healthy Longevity Study (CLHLS, 2008-2018), individuals aged≥65 years having complete data of frailty were recruited. Modified Fried criteria(exhaustion, shrink, weakness, low mobility, inactivity) were adopted to define pre-frailty(1-2 domains) and frailty(≥3 domains), respectively. The association between pre-frailty/frailty and adverse outcomes(frequent hospitalization, limited physical performance, cognitive decline, multimorbidity, dependence) was analyzed using logistic regression models. The association between pre-frailty/frailty and mortality was analyzed using Cox proportional hazards models. Age- and gender-stratified analyses were performed. Results Totally, 13,859 participants aged 85.8±11.1 years, including 2,056 centenarians, were recruited. The overall prevalence of pre-frailty and frailty were 54.1% and 26.3%, respectively. Only 5.0% of centenarians were non-frailty whereas 59.9% of the young-old(65-79 years) showed pre-frailty. Both pre-frailty and frailty were associated with the increased risk of multiple adverse outcomes, such as incident limited physical performance, cognitive decline and dependence, respectively. (P<0.05) Frail males were more vulnerable to the risk of mortality(hazard ratio[HR]=2.3, 95% confidence interval[CI], 2.1-2.6) compared with frail females (HR=1.9, 95%CI, 1.7-2.1). The strongest association between frailty and mortality was observed among the young-old(HR=3.6, 95%CI, 2.8-4.5). Exhaustion was the most common domain among patients with pre-frailty (74.8%) or frailty (83.2%), followed by shrink (32.3%) in pre-frailty and low mobility (83.0%) in frailty. Inactivity among females aged 65-79 years showed the strongest association with the risk of mortality (HR=3.50, 95%CI, 2.52-4.87). Conclusion A huge gap exists between longer life and healthy aging in China. According to the age- and gender-specific prevalence and prognosis of frailty, the strategy of frailty prevention and intervention should be further individualized.